Strategi Pemberdayaan Usaha Mikro Kecil Menengah (UMKM) Pada Masa Pandemi Covid-19 - Heru Eko Pramono; Eka Askafi (REVITALISASI : Jurnal Ilmu Manajemen, 2022)
This research is entitled "Strategy for Empowerment of Micro, Small and Medium Enterprises (MSMEs) During the Covid 19 Pandemic In Blitar City". The impact of covid-19, especially in Blitar City, has caused many economic sectors to experience a decline in turnover and some have even gone out of business. Several food and beverage-based sectors were also affected by the lockdown and PPKM implemented by the government. The economy of the community is sluggish and has an impact on the decline in regional income. The purpose of the study was to find out the description and strategies of MSMEs during the COVID-19 pandemic in Blitar City. The method used is qualitative with SWOT analysis. Based on the results of the study, it was shown that the recommendations for the strategy of MSMEs during the COVID-19 pandemic in Blitar City were based on the results of calculations. QSPM analysis shows that the highest TAS value is an alternative strategy of ""Increasing business capital assistance for MSMEs that remain productive to expand marketing through online sales" and "Providing business capital assistance for affected MSMEs in order to maintain their business conditions"..